2021
DOI: 10.1109/access.2021.3071057
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Auxiliary Classification and Diagnosis of Lung Cancer Subtypes Based on Histopathological Images

Abstract: Lung cancer (LC) is one of the most serious cancers threatening human health. Histopathological examination is the gold standard for qualitative and clinical staging of lung tumors. However, the process for doctors to examine thousands of histopathological images is very cumbersome, especially for doctors with less experience. Therefore, objective pathological diagnosis results can effectively help doctors choose the most appropriate treatment mode, thereby improving the survival rate of patients. For the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 92 publications
(74 reference statements)
0
19
0
Order By: Relevance
“…Hence, we could observe a variation in model performance [76]. In a few studies [45,46], the model performance was less as compared to other lung cancer classification models because of microscopic images from private hospitals with small sized datasets. The studies [10,41,44] reported the use of only cell-level information from the images captured at 40X magnification for classification, which resulted in model accuracy of around 85%.…”
Section: Discussion and Future Directionsmentioning
confidence: 98%
See 4 more Smart Citations
“…Hence, we could observe a variation in model performance [76]. In a few studies [45,46], the model performance was less as compared to other lung cancer classification models because of microscopic images from private hospitals with small sized datasets. The studies [10,41,44] reported the use of only cell-level information from the images captured at 40X magnification for classification, which resulted in model accuracy of around 85%.…”
Section: Discussion and Future Directionsmentioning
confidence: 98%
“…), autoencoders, and customized CNNs top the list. SVM [45,46,67,86,88,95,96,99,108] and RF tree classifier [45,76,80,82,84,86,103,108] were second and third in the list. In the 'Others' category, we included hashing, LR, quasi-supervised learning algorithm, ensemble learning, and linear classifier based on different features extracted from ROI for decision-making.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
See 3 more Smart Citations